Assessment of the sustainability of public finances of the Republic of Kazakhstan - M. K. Kozhahmetova; D. S. Kydyraliev; M. A. Markelova; M. A. Muhametkalieva (Экономика: стратегия и практика, 2020)
The stability of public finances ensures a stable, effective development of the state, and as a result - an increase in the level and quality of life of the population. A country that has domestic sources of financing as the basis for its development has more stable and higher long-term development and growth prospects. The elements of the financial system support and reinforce each other, and the main levers of influence on the economy are within the country. Only in this case it can be argued that the country has long-term financial sovereignty. This article evaluates the sustainability of public finances of the Republic of Kazakhstan based on the calculation of indicators of the financial stability of the state. At the same time, the assessment of the sustainability of public finances in the work is considered from the point of view of the impact of public debt, therefore, structural coefficients of the composition of external and internal debt, which characterize the debt burden, debt dependence of the budget, the citizen of the country, as well as the debt limit, etc. The calculated coefficients based on the data of Kazakhstan were compared with their threshold values, as a result of which a number of conclusions were made about the sustainability of public finances of the Republic of Kazakhstan. In addition, the coefficients were determined that are at the limit at the time of the study, and an increase in which may negatively affect the sustainability of public finances of the Republic of Kazakhstan.